A DECADE (2014–2024) OF MTB-MLE IN THE PHILIPPINES: WHERE IT WORKED, WHERE IT STRUGGLED, AND WHAT COMES NEXT - Lawangen, Micah P.; Pelila, John Rey Osben; Itorma, Mary Grace M.; Ago, Mica C; Nacod-am5, Charlene M.; Macasieb, John Rey N.; Garcia, Ledy S.; Alawas, Jessie James S.; Libalib, Liza G.; Bansan, Gail P.; Buyay, Emily J.; Osting, Eurelle Joyce W. (Sanata Dharma University Yogyakarta, 2025)
Capturing a full decade of language program implementation offers a valuable opportunity to reflect on the evolution, strengths, and limitations of one of the country’s most transformative language-in-education reforms. With the introduction of Mother Tongue-Based Multilingual Education (MTB-MLE) under the Philippine K–12 Curriculum, interest has grown in assessing its accomplishments and ongoing challenges. Therefore, this study aims to review key developments in MTB-MLE implementation from 2014 to 2024. A systematic literature review (SLR) was conducted using peer-reviewed articles and Department of Education documents from academic databases and government archives. Following PRISMA guidelines, 14 documents were selected and analyzed thematically. Findings reveal that strong policy backing, language mapping, and teacher training improved early literacy and student engagement through first language (L1) instruction. However, challenges include limited teacher proficiency, lack of localized materials, policy–practice mismatches, and weak support for second language development. Besides, standardization pressures also clashed with the multilingual realities of classrooms. In conclusion, while MTB-MLE remains a promising reform, it has yet to fulfill its potential due to systemic constraints. Future efforts should adopt more flexible and linguistically responsive strategies, and if unrealized in basic education, MTB-MLE may find greater traction within higher education.